Eichmann e a incapacidade de pensar alienação do mundo e do pensamento em Hannah Arendt - Pereira, Renato de Oliveira (Editora Oficina Universitária, 2021)
The starting point of this book is the Eichmann case, as analyzed by Hannah Arendt in Eichmann in Jerusalem (1963), a work that results from her participation in the trial of the former SS lieutenant colonel responsible for the logistics of transporting Jews to the concentration and extermination camps during the Nazi regime in Germany. As the author shows, the mismatch between the monstrosity of the crimes that Eichmann helped perpetrate and his figure before the court - which did not seem monstrous or malevolent to Arendt, but completely normal and even mediocre - led her to coin the expression banality from evil. With such a notion, Arendt designates a new type of evil, which is not caused by base motives, corrupted instincts or an evil will, but by obedience to the duty of office linked to a refusal of the agent to think about what he does. With the aim of understanding what are the conditions that provide this inability or absence of thinking (thoughtlessness), the author examines, within Arendt's theoretical framework, how not only totalitarian regimes, but also the Modern Era itself, produce the experience of loneliness (loneliness) within mass society. Such an experience undermines the establishment of a common world in which human plurality can be affirmed, a condition for exercising the ability to act, feel and also think.